Karakteristik dan Kemelimpahan Nepenthes di Habitat Miskin Unsur Hara - Mardhiana Mardhiana; Yakup Parto; Renih Hayati; Dwi Putro Priadi (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2012)
Mardhiana et al., 2012. The Characteristics and Abundance of Nepenthes of Nutrient-poor Habitats. JLSO 1(1):50-56.This research aimed at assesing the characteristics and abundanceof Nepenthespopulation in nutrient-poor habitats. This study was conducted at two locations, Talang Kelapa village, Banyuasin Km 10, and Pasir Putih village, Sukajadi, Banyuasin Km 18. Observations were made on the soil chemical and physical properties, morphology and population abundance of Nepenthes. The result showed that N. mirabilis was the only species found in Talang Kelapa and Pasir Putih. Nepenthes upwere able to grow well in very poor soil nutrients. Natural habitat in Pasir Putih with sandy soil and water log condition gave better effect on the morphology and abundance in than in Talang Kelapa with clay soil and dry. The ratio of Nepenthes abundance in Pasir Putih to that in Talang Kelapa was 3:2.